ANALISIS DAN PERANCANGAN SISTEM ABSENSI GURU DAN SISWA DENGAN PENDEKATAN BERORIENTASI OBJEK MENGGUNAKAN UML (STUDI KASUS: SMA NEGERI 7 BOGOR) - Jaenudin, Jejen; Al-Ikhsan, Safaruddin Hidayat; Ardiansyah, Dicky (Krea-TIF: Jurnal Teknik Informatika, 2014)
The advancement of information technology has offered a phenomenal functional impact on every aspects of human life, one such is usage of Information Technology at schools. Loss of data due to manual record keeping is still prevailing in many schools, SMA NEGERI 7 BOGOR is not an exception. The aim of this research is to design an interface for SMA NEGERI 7 BOGOR which can facilitate and secures student and teacher`s data. In this research, Unified Modeling Language (UML) is used as a tool for designing the interface system using context diagram, use case diagram, class diagram, activity diagram, and sequence diagram. Using this interface system an update, well documented and safe data can be maintained. This should facilitate in monitoring of student and teachers attendance.